Is Fatty Liver Associated With Depression? A Meta-Analysis and Systematic Review on the Prevalence, Risk Factors, and Outcomes of Depression and Non-alcoholic Fatty Liver Disease - Xiao, Jieling; Lim, Lincoln Kai En; Ng, Cheng Han; Tan, Darren Jun Hao; Lim, Wen Hui; Ho, Cyrus S. H.; Tan, Eunice Xiang Xuan; Sanyal, Arun J.; Muthiah, Mark D. (Frontiers in Medicine, 2021)
Background and Aims: Both non-alcoholic Fatty Liver Disease (NAFLD) and depression have a high global prevalence which is projected to increase further. While studies exploring the association have been done, there is conflicting data. This study aims to assess the prevalence and association between depression and NAFLD. Methods: Medline and Embase were searched from inception to 3 March 2020. Meta-analysis of proportions using the generalized linear mix model was conducted to analyse the pooled prevalence of depression in NAFLD patients. Risk factors for depression in NAFLD patients were evaluated in conventional pairwise meta-analysis. Results: 10 studies involving 2,041,752 NAFLD patients were included. Pooled prevalence of depression was 18.21% (CI: 11.12% – 28.38%) in patients with NAFLD and 40.68% (CI: 25.11% - 58.37%) in patients with non-alcoholic steatohepatitis (NASH). NAFLD resulted in significantly higher risk of development of depression (OR: 1.29, CI: 1.02 – 1.64, p=0.03). NASH patients had a significantly higher risk of depression compared to NAFLD patients (RR: 2.83, CI: 2.41 – 3.32, p<0.001). Diabetes, body mass index (BMI), female sex, smoking, and history of pulmonary disease were significant risk factors for depression in NAFLD patients. Conclusion: This study demonstrated a high prevalence of depression in NAFLD patients, and a significant association between both conditions. Furthermore, patients with NASH had a significantly higher risk of depression compared to NAFLD. Diabetes, BMI, history of lung disease or smoking and female gender were significant risk factors. Further studies investigating the pathophysiological mechanism underlying depression and NAFLD are needed.